Ethical Leadership Assessment for The Islamic Secondary School Principals - Ristapawa Indra; Martin Kustati (Jurnal Pendidikan Islam, 2019)
This study aims to determine the assessment of ethical leadership in Islamic High School principal; determine the relationship among ethical leadership constructs; and investigates the influence of ethical leadership in terms of value, serve, act justly, and do right to build the community for a common goal. Eight Islamic secondary schools and 80 teachers were selected as respondents for the study. Quantitative data obtained through a questionnaire which is modified from ethical leadership Perceived Leader Instrument Integrity Scale (LIS). The questionnaire was analyzed using mean and standard deviation, Pearson correlation, and path analysis with multiple regressions. The findings show that the assessment of ethical leadership matched with empirical data. It also found that leadership principals in the service of others was developed at the level of an ethical community, and in terms of respect for others is at unethical level. Then, the finding showed that each construct correlated at a moderate level. It also found that the constructs of ethical leadership (serve and act) provided direct influence on the establishment of a community development effort. The study recommended the elements of ethical leadership of respect for others.